The Book of Revolutions the battles of priests, prophets, and kings that birthed the Torah - Feld, Edward 1943- (Lincoln University of Nebraska Press, 2022)
The Book of Revolutions unveils the epic saga of ancient Israel as the visionary legacy of inspired authors in different times and places, and the Torah as an emblem of pluralistic belief born of three revolutionary moments in history.
Cover -- Title Page -- Copyright Page -- Contents -- List of Illustrations -- Acknowledgments -- Introduction -- Prelude: Origins of the People Israel -- Part I. Revolution in Northern Israel -- 1. Elijah's Victory -- 2. The Covenant Code -- 3. The Heritage of the Covenant Code -- First Interlude: In Judea -- Part II: Revolution in Judea -- 4. Years of Turmoil -- 5. Josiah and the Book of Deuteronomy -- 6. Law in Deuteronomy -- 7. Deuteronomy's Revelation -- 8. The People and the Land -- 9. The Heritage of Deuteronomy -- Second Interlude: The End of Monarchy -- Part III: Revolution in Babylonia -- 10. Priests, Prophets, and Scribes in Exile -- 11. The Holiness Code -- 12. The Heritage of the Holiness Code -- Part IV. The Last Revolution -- 13. The Torah -- Final Thoughts -- Notes -- Bibliography -- Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books